Lower body stiffness modulation strategies in well trained female athletes - Millett, E. L.; Moresi, M. P.; Watsford, M. L.; Taylor, P. G.; Greene, D. A. (The Journal of Strength and Conditioning Research, 2016)
Lower extremity stiffness quantifies the relationship between the amount of leg compression and the external load to which the limb are subjected. This study aimed to assess differences in leg and joint stiffness and the subsequent kinematic and kinetic control mechanisms between athletes from various training backgrounds. Forty-seven female participants (20 nationally identified netballers, 13 high level endurance athletes and 14 age and gender matched controls) completed a maximal unilateral countermovement jump, drop jump and horizontal jump to assess stiffness. Leg stiffness, joint stiffness and associated mechanical parameters were assessed with a 10 camera motion analysis system and force plate. No significant differences were evident for leg stiffness measures between athletic groups for any of the tasks (p = 0.321-0.849). However, differences in joint stiffness and its contribution to leg stiffness, jump performance outcome measures and stiffness control mechanisms were evident between all groups. Practitioners should consider the appropriateness of the task utilised in leg stiffness screening. Inclusion of mechanistic and/or more sports specific tasks may be more appropriate for athletic groups.